A statement by the sun: a Practice-as-Research enquiry into presence and absence - Piazzoli, Erika; Cañas, Tania (My University, 2026)
This article describes a Practice-as-Research (PaR) project, involving a group of young people in drama and visual arts practices, to explore their understandings of absence and presence in the community. The data, including the facilitators’ reflection of the drama workshops, students’ artwork, photographs, interviews, and a focus group, was analysed through reflexive Thematic Analysis (Braun and Clarke, 2022) integrated with poetic enquiry (Faulkner, 2019) and ethnodrama (Salvatore, 2025). The article starts by delineating the main elements of PaR methodology (Candy et al, 2022; Nelson, 2022), an approach to enquiry grounded in artistic processes that prioritises embodied knowledge, affective experience, and multimodal forms of expression. Next, the article draws on Kershaw et al’s (2011) five dimensions of PaR to delineate the abSENce–presenCE (SENCE) study. The discussion traces how the initial thematic prompt of ‘presence’, at the heart of the study, evolved through the practice into a dramaturgical framework for exploring the relational dynamics, and ultimately into a methodology of PaR itself. This trajectory informed every stage of the project, from data generation through to analysis and dissemination, demonstrating how PaR shaped the research process holistically. The findings highlight the significance of positioning PaR as a methodology that drove the entire research process, generating plural practices that sustained ongoing engagement. Importantly, we argue that PaR can be applied not only by established artists, but also by community groups and young people, centring them as makers and enabling active participation in the interpretive dimensions of research.
PUBLISHED
Keywords: Practice as Research; abSENce; presenCE, poetic enquiry, ethnodrama; Creative Arts Practice; Arts in Education; Drama and theatre in education; Visual Arts